REVENUE SHARING FUND OF TOBACCO PRODUCTS EXCISE AND ECONOMIC PERFORMANCE IN DECENTRALIZED ERA - Yandri, Pitri; Budi, Sutia; Sujatna, Yayat; Masduki, Uki (Journal of Governance and Public Policy, 2020)
For the regions that have tobacco farming, the tobacco has economic potential for them. It means that the better the productivity of tobacco farming, the better the regional economy will be. The government has, therefore, set up the Revenue Sharing Fund of Tobacco Products Excise scheme to drive tobacco agricultural productivity in every area that produces tobacco. This study uses an econometric approach to examine the effect of DBHCHT on the regional economy, both aggregate and sectoral in Rembang Regency. Rembang Regency is known as one of the tobacco producers in Central Java. The economic sectors analyzed are the agriculture, industry, and health sectors. The results show that DBHCHT has a positive effect, both aggregate and sectoral, with varying degrees of magnitude. Further collaborations on these results are entirely presented in this article.